Air quality in New York City hookah bars. Issue Volume 24:Issue e3(2015) (16th September 2014) - Zhou, Sherry; Weitzman, Michael; Vilcassim, Ruzmyn; Wilson, Jennifer; Legrand, Nina; Saunders, Eric; Travers, Mark; Chen, Lung-Chi; Peltier, Richard; Gordon, Terry
Abstract : Background: Hookahs are increasingly being used in the USA and elsewhere. Despite the popularity of hookah bars, there is a paucity of research assessing the health effects of hookah smoke, and although New York City (NYC) bans indoor tobacco smoking, hookah lounges claim that they only use herbal products without tobacco. This study investigated levels of multiple indices of indoor air pollution in hookah bars in NYC. Methods: Air samples were collected in 8 hookah bars in NYC. Along with venue characteristics, real-time measurements of fine particulate matter (PM2.5 ), black carbon (BC), and carbon monoxide (CO), and total gravimetric PM, elemental carbon (EC), organic carbon (OC), and nicotine were collected in 1-2 hour sessions. Results: Overall, levels of indoor air pollution increased with increasing numbers of active hookahs smoked. The mean (SD) real time PM2.5 level was 1179.9 (939.4) µg/m 3, whereas the filter-based total PM mean was 691.3 (592.6) µg/m 3 . The mean real time BC level was 4.1 (2.3) µg/m 3, OC was 237.9 (112.3) µg/m 3, and CO was 32 (16) ppm. Airborne nicotine was present in all studied hookah bars (4.2 (1.5) µg/m 3 ). Conclusions: These results demonstrate that despite the ban on smoking tobacco products, at the very least, some NYC hookah bars are serving tobacco-based hookahs, and have elevated concentrations of indoor air pollutants that may present a health threat to visitors and employees. Therefore, there is an urgent need for better air quality monitoring in such establishments and policies to combat this emerging public health threat.